First results with 3-strap ICRF antennas in ASDEX Upgrade. (5th July 2016) - Bobkov, V.; Braun, F.; Dux, R.; Herrmann, A.; Faugel, H.; Fünfgelder, H.; Kallenbach, A.; Neu, R.; Noterdaeme, J.-M.; Ochoukov, R.; Pütterich, Th.; Tuccilo, A.; et al.
Abstract: The 3-strap antennas in ASDEX Upgrade allow ICRF operation with low tungsten (W) content in the confined plasma with W-coated antenna limiters. With the 3-strap antenna configuration, the local W impurity source at the antenna is drastically reduced and the core W concentration is similar to that of the boron coated 2-strap antenna at a given ICRF power. Operation of the 3-strap antennas with the power ratio between the central and the outer straps of 1.5 : 1 and 2 : 1 is adopted to minimize the ICRF-specific W release.